The partial slip contact problem for a monoclinic coated half plane - Çömez, I.; Alinia, Y.; Güler, M.A. (Archives of Mechanics, 2022)
In this study, the partial slip contact problem for a monoclinic coated half plane indented by a rigid cylindrical punch is considered. The main objective of current study is to illustrate the effects of material anisotropy on the surface stresses, the contact width and the stick/slip region of the partial slip contact. Using the Fourier integral transform and boundary conditions of the problem, the singular integral equation of the system is obtained. Numerical results of the problem are provided for typical fibrous composites applying the Gauss-Chebyshev discretization method. Sensitivity analysis of the surface stresses is performed for both the material and geometric parameters. The results indicate that the coating fiber angle can significantly alter the distribution of contact tractions. As the fiber angle ranges from θ = 0° to θ = 90°, the contact half-length increases up to 20% whereas the stick zone half-length varies significantly.